Field test on the palatability of the subterranean termites to pine wood with various treatments - Arinana Arinana; Ahmad Fannani; Dodi Nandika; Noor Haneda (Society for Indonesian Biodiversity, 2020)
Abstract. Ariana, Fannani AR, Nandika D, Haneda NF. 2020. Field test on the palatability of the subterranean termites to pine wood with various treatments. Biodiversitas 21: 5763-5771. One of the keys to successfully determining the subterranean termite species' diversity in an area is using wood samples of their preference. This research aimed to evaluate the palatability of the subterranean termites to pine wood (Pinus merkusii) with boiling, steaming, hot vapor pressure, and oven treatments in the Arboretum of the Faculty of Forestry, IPB University, Bogor, West Java, Indonesia, and to analyze the species and the distribution of the subterranean termites that attacked the samples. The wood samples were 2 cm x 2 cm x 46 cm in size (ASTM D 1758-06). The steaming (100°C), boiling (100°C), and hot vapor pressure (1 bar, 105°C) treatments were carried out for five hours, while the oven treatment (103±2°C) was set up for 48 hours. Wood samples without treatment were also prepared as a control. After the treatments, all the samples were air-dried, sanded, weighed, and installed in the research location. The results showed that four subterranean termite species, i.e., Schedorhinotermes sp., Microtermes sp., Capritermes sp., and Macrotermes sp, were found attacking the wood samples. The highest attack frequency and the highest damage intensity were found in wood samples with hot vapor pressure treatment. Based on the scoring, the preeminent treatment for the wood samples was the hot vapor pressured treatment.